Can Microfinance Create Positive Economic Impact on its Beneficiaries? A Theoretical Review - Murrla, Prlyanka; Verma, Satish (Gyan Management Journal, 2014)
The development of any economy is a function of aggregate of income generating activities and distribution of economic gains among the masses. It involves an assessment of the inclusiveness of economic growth of not only masses in premium income segment but also those who lie in low or lower income segment. These represent those people who do not have collateral security in order to obtain loan and hence, have somehow been excluded from the formal financial structure. In order to achieve this objective, reduction of poverty has explicitly been defined as one of the key elements in the much talked "inclusive growth" strategy of twelfth five year plan. In the recent years, microfinance is being increasingly utilized as a nostrum for poverty alleviation.The paper starts with the objective and the rationale for the study. In the next sections it discusses the role of microfinance in creating economic impact on the lives of poor masses. Paper concludes with identifying the gaps in literature and also suggests some future directions of research followed by a brief conclusion.
Keywords: Inclusive growth; Income Generating Activities; Microfinance; Nostrum